Notes from the rehearsal room a director's process - Meckler, Nancy (London, UK Methuen Drama, 2023)
"Renowned theatre and film director Nancy Meckler delves into her hugely varied experiences in the rehearsal room and shares examples of some of her tried-and-tested "tools" that she utilises when bringing a play to life. Meckler encourages you to interrogate, play, experiment and to use her methods as a starting point to begin creating your own unique directing toolkit. This book therefore is not intended to offer a singular step-by-step process, but to empower you to find your own style. The examples are drawn from her experience directing a range of work from classic plays, including work by Chekov, Brecht and Shakespeare, to new writing, including work by Pam Gems and Sam Shephard, and in a wide range of renowned theatres, including the RSC, National Theatre, Royal Court and a number of the UK's regional theatres. Drawing on her methods of improvisation, interrogation and exploration, Meckler details how she approaches: text concept creative design elements actors ensemble genre relationships with designers designing for a specific space casting process rehearsal scheduling working with contemporary and first-time writers working on comedy ... among many other areas. She offers specific techniques along with practical guidance to complement a director's work at any stage of their career. The author's approachable and relatable writing style enables an in-depth look into how she works with actors and the many ways in which she may approach a new project while also providing us with a unique insight into her own wealth of experience over a remarkable career as an award-winning and internationally celebrated director"--Provided by publisher.
Preparation -- The concept -- Keystones -- Improvisation -- Rehearsal process -- The mystery of comedy -- Collaboration -- Discovering physical theatre and working in different mediums -- Epilogue.
Includes index.
Keywords: Theater -- Production and direction